Effectiveness Of Inheritance Dispute Resolution Through Non-Litigation Channels - Iswanto Malik (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2022)
The effectiveness of law enforcement is closely related to the effectiveness of the law. In order for the law to be effective, law enforcement officers are needed to enforce these sanctions. A sanction can be actualized to the community in the form of compliance, with these conditions showing indicators that the law is effective. In resolving disputes through non-litigation, we have recognized the existence of alternative dispute resolution or Alternative Dispute Resolution (ADR), which is described in Article 1 number (10) of Law Number 30 of 1999 concerning Arbitration and ADR, which reads as follows: Alternative Dispute Settlement is an institution for resolving disputes or differences of opinion through procedures agreed upon by the parties, namely dispute resolution out of court by means of consultation, mediation, conciliation, or expert judgment. The approach used in this research is a qualitative approach. The type of research used in this study is a case study. Results In the method of village arbitration in the settlement of inheritance disputes 1) village heads and village officials have an important role in the settlement of inheritance disputes, namely as mediators, including: opening and leading the mediation process, explaining, providing advice and the best solution, deciding and determining what the parties have agreed upon. dispute, prevent the emergence of a larger dispute 2) settlement of inheritance disputes by arbitration is quite effective in resolving inheritance disputes in the village, in resolving disputes through mediation, the parties are able to reach an agreement between them, so that the benefits of mediation are felt with minimal costs. issued and the time that is not long also reduces conflicts between heirs.